Why Is Pi Less Than Twice Phi?. Issue 8 (14th September 2018) - Morales, Alejandro H.; Pak, Igor; Panova, Greta
Abstract : We give a proof of the inequality in the title in terms of Fibonacci numbers and Euler numbers via a combinatorial argument and asymptotics for these numbers. The result is motivated by Sidorenko's theorem on the number of linear extensions of a partially ordered set and its complement. We conclude with some open problems.